Differences of Lower Urinary Tract Symptoms Degree In Benign Prostatic Hyperplasia Patients With and Without Diabetes Mellitus - Clarissa, Jeannis; Warli, Syah Mirsya; Dhirajaya Dharma Kadar; Nurfida Khairina Arrasyid (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2021)
Background. Benign Prostatic Hyperplasia (BPH) is a benign tumor that most often occurs in men. Many risk factors could cause BPH, one of which is diabetes mellitus (DM). Diabetes mellitus (DM) is a metabolic disease, characterized by hyperglycemia. Method. This study was conducted at the Urology Polyclinic of the UniversitasÂ  Sumatera Utara Hospital from August to September 2019. A total of 102 patients diagnosed with BPH were registered by cross-sectional study approach. Detailed medical history and physical examination were performed for all patients to diagnose BPH. While the diagnosis of DM was according to patient history or diabetic-medicine use. International Prostate Symptom Score (IPSS) were completed by all patients to obtain a LUTS degree. Result. From a total of 102 patients diagnosed with BPH there were 97 patients were selected. The mean age of patients was 70.43 Â± 7.52 year (range 50-88 year) and the total IPSS score was 17.55 Â± 6.55. DM patients were more likely to report severe LUTS and the symptom score evaluated with IPSS was signiï¬cantly higher than in non non-DM group: 21.69 Â± 5.41 vs 16.70 Â± 6.41 (p=0.005). For the IPSS subscores, the DM group also show higher storage: 8.38 Â± 4.57 vs 5.88 Â± 3.72 (p = 0.02), voiding: 9.69 Â± 2.47 vs 8.14 Â± 3.21, (p= 0.039) and post micturition: 3.63 Â± 1.26 vs 2.69 Â± 1.744, (p= 0.045) symptoms significantly. Conclusion: Benign Prostatic Hyperplasia patients with DM manifested more severe lower urinary tract symptoms. Storage, voiding, post micturition, and urgency symptoms were also greater.